NK cell-mediated cytotoxicity modulation by A(2) adenosine receptor agonist in different mammalian species - Kuldová, M; Svoboda, J; Kovárů, F; Vannucci, L; Kovárů, H; Fiserová, A (Folia microbiologica, 2009)
Adenosines, endogenous purine nucleosides, appear in the extracellular space under metabolically stressful conditions associated with ischemia, inflammation, and cell damage. Their activity on innate immunity is prevalently inhibitory and can develop both in infectious and neoplastic diseases. During cancer development, tumor cells that release high concentrations of adenosines can impair the function of tumor-infiltrating lymphocytes and assist tumor growth by neo-angiogenesis. We evaluated the influence of A(2) adenosine receptor (A(2)AR) agonist on cytotoxic-cell response comparing human with other mammalian species (rodents, pigs, goats), both in healthy and in cancer conditions. The A(2)AR agonist developed dose-dependent inhibition of the cytotoxic activity of immune effector cells in all studied species. However, variability of the response was observed in relation to the species and the target cells that were used. Altogether, our data indicate that the A(2)AR plays a central role in adenosine-mediated inhibition of immune response to tumors.
Keywords: prasata; kozy; adenosin; hlodavci; Swine; Male; Rats, Wistar; Neoplasms; Adenosine A2 Receptor Agonists; Goats; Rodentia; agonisté adenosinového receptoru A2; mužské pohlaví; potkani Wistar; receptory adenosinové A2; cytotoxicita imunologická; krysa rodu Rattus; kultivované buňky; Animals; lidé; ženské pohlaví; Humans; zvířata; buňky NK; Rats; myši inbrední C57BL; myši; Mice, Inbred C57BL; Cells, Cultured; nádory; Adenosine; Female; Killer Cells, Natural; Mice; Cytotoxicity, Immunologic; Receptors, Adenosine A2